Quantifying Nutrient Budgets for Sustainable Nutrient Management. Issue 3 (2nd March 2020) - Zhang, X.; Davidson, E. A.; Zou, T.; Lassaletta, L.; Quan, Z.; Li, T.; Zhang, W.
Abstract: Nutrients, such as nitrogen and phosphorus, provide vital support for human life, but overloading nutrients to the Earth system leads to environmental concerns, such as water and air pollution on local scales and climate change on the global scale. With an urgent need to feed the world's growing population and the growing concern over nutrient pollution and climate change, sustainable nutrient management has become a major challenge for this century. To address this challenge, the growing body of research on nutrient budgets, namely the nutrient inputs and outputs of a given system, has provided great opportunities for improving scientific knowledge of the complex nutrient cycles in the coupled human and natural systems. This knowledge can help inform stakeholders, such as farmers, consumers, and policy makers, on their decisions related to nutrient management. This paper systematically reviews major challenges, as well as opportunities, in defining, quantifying, and applying nutrient budgets. Nutrient budgets have been defined for various systems with different research or application purposes, but the lack of consistency in the system definition and its budget terms has hindered intercomparison among studies and experience‐sharing among researchers and regions. Our review synthesizes existing nutrient budgets under a framework with five systems (i.e., Soil‐Plant system, Animal system, Animal‐Plant‐Soil system, Agro‐Food system, and Landscape system) and four spatial scales (i.e., Plot and Farm, Watershed, National, and Global scales). We define these systems and identify issues of nitrogen and phosphorus budgets within each. Few nutrient budgets have been well balanced at any scale, due to the large uncertainties in the quantification of several major budget terms. The type and level of challenges vary across spatial scales and also differ among nutrients. Improvement in nutrient budgets will rely not only on the technological advancement of scientific observations and models but also on better bookkeeping of human activity data. While some nutrient budget terms may need decades, or even centuries, of research to be well quantified within desirable levels of uncertainties, it is imperative to effectively communicate to interested stakeholders our understanding of nutrient budgets so that scientists and a variety of stakeholders can work together to address the sustainable nutrient management challenge of this century. Plain Language Summary: Managing nutrients, such as nitrogen and phosphorus, is fundamental, yet challenging, for sustainable development. Nutrients are critical for plant and animal growth in agriculture and in nonagricultural ecosystems and are consequently important for food security and climate stability, as well as human health. However, historical and ongoing increases in nutrient inputs to agriculture, while increasing food production, have also contributed to severe environmental problems, ranging from local water and air pollution to global climate change. Quantifying the nutrient inputs and outputs of a farm, watershed, or any other well‐defined boundary advances our knowledge of how to maintain a nutrient balance, which is an essential step toward sustainable nutrient management. So far, many research efforts have been devoted to quantifying nutrient budgets and to improving nutrient management for different systems (e.g., farms and food supply chains) and at different spatial scales (e.g., from a single farm to the entire world). However, due to the complex nature of nutrient cycles and incomplete data sets, challenges remain in quantifying and understanding nutrient budgets to inform policies and actions for sustainable nutrient management. With a systematic review of major challenges in defining, quantifying, and applying nutrient budgets, this paper calls for collective efforts by researchers, farmers, watershed managers, consumers, policy makers, and other stakeholders involved in nutrient management to improve our ability to balance nutrient budgets and to use that understanding to grow abundant food while avoiding pollution. Key Points: Sustainable nutrient management, a major challenge of this century, requires better quantification of nutrient budgets This paper reviews major challenges in defining, quantifying, and applying nutrient budgets on multiple system and spatial scales The improvement and limitation in nutrient budgets need to be communicated among researchers and stakeholders to enable positive changes